Post-COVID Syndrome in Children: One-Time Survey Study of Parents' Opinion - Dilara R. Shagieva; Mansur A. Kutlubaev; Airat R. Rakhmatullin ("Paediatrician" Publishers LLC, 2023)
Background. COVID-19 symptoms often persist for a long time, it indicates the post-COVID syndrome development. Its frequency in children population is generally studied by interviewing the children themselves. This approach limits the risk evaluation of post-COVID syndrome development in young children who are unable to describe the persistent symptoms due to their age.Objective. The aim of the study is to evaluate the prevalence of post-COVID syndrome in children and its effect on their daily activities by interviewing parents.Methods. The survey covered parents of children (aged from 3 months to 18 years) who suffered laboratory-confirmed COVID-19 in 2021-2022 but not earlier than 12 weeks before study initiation. The survey was conducted on-line. The presence of the symptoms (persisted or occurred 12 weeks after COVID-19), its impact on children's daily life, the need for medical treatment or doctor's advice (due to these post-covid symptoms) and vaccination against novel coronavirus infection were evaluated. Incidence of post-COVID syndrome was analyzed in subgroups based on sex, age (< 3 years, 3-6 and 7-17 years), and disease severity.Results. Invitations to participate in the study were sent to 2292 parents of all children registered at the clinic and suffered from COVID-19 via WhatsApp and Telegram messengers. 1533 (66.9%) of them agreed to take part in the survey, and 1258 (54.8%) filled out the questionnaire in full. The survey has revealed that at least one symptom that persisted or occurred 12 weeks after COVID-19 was noted by parents in 764 out of 1258 (60.6%) children (more often in the older age group and in severe cases). Significant negative impact of symptoms on children's daily life was noted by 251 out of 764 (32.9%) respondents. Parents of 734 out of 764 (96.1%) children have visited a doctor due to post-COVID syndrome symptoms.Conclusion. Post-COVID syndrome develops in more than 60% of children after laboratory-confirmed COVID-19, according to parents. However, we have reasons to believe that parental estimations could overestimate the prevalence of post-COVID syndrome.